Pengembangan Fikih Indonesia (Studi Terhadap Kajian Fiqih di Ma’had Aly Salafiyah Syafi’iyyah Situbondo) - Akmal Bashori (Jurnal Hukum Islam, 2017)
Empiricism is a philosophy doctrine that emphasizes the role of experience in acquiring knowledge in excavation of Islamic law (istidlal) or known as al- tajribat al-hissiyat. This method departs from the induction field observations, and the reality of a society as the main source for legislation jurisprudence by using the senses and the intellect. Imam Shafi’i himself uses this method of digging the legal and produces two different opinions; qaulqadim and qauljaded. Similarly, Ma’had Aly Situbondo, Islamic legal thought the product was much influenced by the reality of Indonesian society. The results of this study found that Ma’had Aly (1) in the excavation law always look at the empirical reality (2) MA successfully develop jurisprudence in Indonesia by revitalizing the epistemology of classical Islamic law, the text diversification, expansion of the concept of ta’wil and reconstruction schools of thought (Madhab).